Catechol siderophores repress the pyochelin pathway and activate the enterobactin pathway in Pseudomonas aeruginosa: an opportunity for siderophore–antibiotic conjugates development. (5th February 2016) - Gasser, Véronique; Baco, Etienne; Cunrath, Olivier; August, Pamela Saint; Perraud, Quentin; Zill, Nicolas; Schleberger, Christian; Schmidt, Alexander; Paulen, Aurélie; Bumann, Dirk; Mislin, Gaëtan L. A.; Schalk, Isabelle J.
Summary: Previous studies have suggested that antibiotic vectorization by siderophores (iron chelators produced by bacteria) considerably increases the efficacy of such drugs. The siderophore serves as a vector: when the pathogen tries to take up iron via the siderophore, it also takes up the antibiotic. Catecholates are among the most common iron‐chelating compounds used in synthetic siderophore–antibiotic conjugates. Using reverse transcription polymerase chain reaction and proteomic approaches, we showed that the presence of catecholate compounds in the medium of P seudomonas aeruginosa led to strong activation of the transcription and expression of the outer membrane transporter PfeA, the ferri‐enterobactin importer. Iron‐55 uptake assays on bacteria with and without PfeA expression confirmed that catechol compounds imported iron into P . aeruginosa cells via PfeA. Uptake rates were between 0.3 × 10 3 and 2 × 10 3 Fe atoms/bacterium/min according to the used catechol siderophore in iron‐restricted medium, and remained as high as 0.8 × 10 3 Fe atoms/bacterium/min for enterobactin, even in iron‐rich medium. Reverse transcription polymerase chain reaction and proteomic approaches showed that in parallel to this switching on of PfeA expression, a repression of the expression of pyochelin (PCH) pathway genes (PCH being one of the two siderophores produced by P . aeruginosa for iron acquisition) was observed.